Peran Audit Internal dalam Upaya Mencegah dan Mendeteksi (Fraud) - Suci Indah Permata; Monika Handayani (P3M Politeknik Negeri Banjarmasin, 2024)
Fraud is often revealed in various ways and employees are the ones who most often report it. Fraud can occur due to influencing factors such as pressure, opportunity and rationalization. The purpose of this study was to determine the effect of the role of internal audit in efforts to prevent and detect fraud and how the internal control system is influenced. This research uses a literature review method with a qualitative descriptive approach. The data source used is secondary data that has been processed to describe the research problem. Based on the analysis of the results of the study, it shows that the role of internal audit and strong internal control is very important to ensure that all business plans in a company run in accordance with the company's predetermined objectives and these steps can also improve operational efficiency, transparency, accountability, and prevent the risk of fraud.